The comparison of two types of physiotherapy techniques on selected weaning indices of patients requiring mechanical ventilation: a single blind randomized controlled trial - Fatemeh Azimi; Amir Mohamad Nazari; Farokh Yadollahi; Shahram Etemadifar; Soleiman Kheiri; Reza Masoudi (Scientific Reports)
Abstract Chest physiotherapy, a key component of bronchial hygiene therapy, plays an important role in the overall management and care of patients who require Mechanical Ventilation (MV). We compared the effects of two types of physiotherapy techniques on selected weaning indices of patients requiring MV. We conducted a single-blind randomized controlled clinical trial with pre- and post-measurements in 60 patients requiring MV. Randomization was performed via block randomization with Sequential Numbered Opaque Sealed Envelopes. Participants were randomized into (1) lung squeezing technique (LST) or (2) chest vibration and percussion technique (CVPT). Data collection was carried out using a researcher-created checklist that comprised two sections. The first section gathered patient demographic information, while the second section functioned as a vital sign record sheet. This vital sign record was further divided: the initial part documented systolic and diastolic blood pressure, pulse rate, oxygen saturation, and RSBI prior to the intervention, and the follow-up part captured the same vital signs at intervals of 5- and 25-minutes post-intervention. There was no statistically significant difference between systolic and diastolic blood pressure, respiratory rate, and oxygen saturation scores of the two study groups at baseline and at 5- and 25-minute intervals post-intervention (P > 0.05). However, in terms of rapid, shallow breathing index (RSBI), a significant difference was observed between the two groups scores at baseline (LST: 38.5 (36.2–44.1) vs. CVPT: 35.2 (33.7–38); P < 0.0), 5-minutes post-intervention (LST: 36.6 (34.3–44) vs. CVPT: 34.8 (32.2–36.9); P < 0.05) and 25-minutes post-intervention (LST: 37.1 (32.5–44.4) vs. CVPT: 34 (32.5–35.8); P < 0.05). The results demonstrated that LST outperformed CVPT in enhancing the RSBI, which serves as a weaning index for patients requiring MV. This suggests that LST may facilitate earlier weaning and extubation for these patients. IRCT20091215002861N18, 09/12/2022. Trial Registration Number: IRCT20091215002861N18, 09/12/2022.